The Impact of Improving Students’ Vocabulary Mastery through Telling Daily Activities among Grade X Students of Vocational School - Zulkarnain, Iskandar; Wahab, Abdul; Hendriani, Ria (Tirai Edukasi : Jurnal Pendidikan, 2024)
This study investigates the effectiveness of the "Telling Daily Activity “Technique in improving English vocabulary mastery among Grade X students of SMK Pariwisata Arruhul Jadiid Tanak Beak in the academic year 2025/2026. Employing a quantitative approach with a pre-experimental design (One Group Pretest-Posttest), the research involved 14 students. Data were collected using vocabulary tests, interviews, and classroom observations. Findings indicate that the average pre-test score was 46.78, while the post-test average increased significantly to 70.35. A paired sample t-test revealed a t-count of 4.704 with a significance level of 0.000 (<0.05), confirming a significant difference between pre-test and post-test scores. These results demonstrate that telling daily activities is effective in enriching students’ vocabulary, enhancing confidence, motivation, and active classroom participation. The study affirms the importance of contextual learning strategies in language acquisition at vocational schools.